IMPLEMENTASI LARAVEL 8.0 PADA MEDIA PEMBELAJARAN E-LEARNING STUDI KASUS STIKOM EL RAHMA BOGOR: IMPLEMENTASI LARAVEL 8.0 PADA MEDIA PEMBELAJARAN E-LEARNING STUDI KASUS STIKOM EL RAHMA BOGOR - Rahmita, Suhendra Anjar Dinata, Deni Muharam (Sekolah Tinggi Ilmu Komputer El Rahma, 2023)
El Rahma High School of Computer Science is an educational institution that does not yet have its own learning media system, still relying on free platforms such as google classroom, in this sophisticated era the learning system has also become very varied. The goal is to create a learning media system to make it easier for students to carry out the learning process, as well as to even out the acceptance of material with one media. The method used in making this learning media system is Research & Development. This learning media system is made with Laravel version 8 software, and PHP MySql.